P‐wave parameters and their association with thrombi and spontaneous echo contrast in the left atrial appendage. Issue 4 (17th February 2023) - Kreimer, Fabienne; Backhaus, Julian Felix; Krogias, Christos; Pflaumbaum, Andreas; Mügge, Andreas; Gotzmann, Michael
Abstract: Background: The aim of this study was to examine the prevalence of abnormal P‐wave parameters in patients with thrombus and/or spontaneous echo contrast (SEC) in the left atrial appendage (LAA), and to identify P‐wave parameters particularly associated with thrombus and SEC formation. Hypothesis: We presume a significant relationship of P‐wave parameters with thrombi and SEC. Methods: All patients in whom a thrombus or SEC was detected in the LAA on transoesophageal echocardiography were included in this study. Patients at risk (CHA2DS2‐VASc Score ≥3) and routine transoesophageal echocardiography to exclude thrombi served as the control group. A detailed ECG analysis was performed. Results: Of a total of 4062 transoesophageal echocardiographies, thrombi and SEC were detected in 302 patients (7.4%). Of these patients, 27 (8.9%) presented with sinus rhythm. The control group included 79 patients. There was no difference in mean CHA2DS2‐VASc score in the two groups ( p = .182). A high prevalence of abnormal P‐wave parameters was detected in patients with thrombus/SEC. Indicators for the presence of thrombi or SEC in the LAA were P‐wave duration >118 ms (Odds ratio (OR) 3.418, Confidence interval (CI) 1.522–7.674, p < .001), P‐wave dispersion >40 ms (OR 2.521, CI 1.390–4.571, p < .001) and advanced interatrial block (OR 1.431, CI 1.033–1.984, p = .005). Conclusion: Our study revealed that several P‐wave parameters are associated with thrombi and SEC in the LAA. The results may help identify patients who are at particularly high risk for thromboembolic events (e.g., in patients with embolic stroke of undetermined source). Abstract : Several P‐wave parameters are associated with atrial fibrillation and with ischemic stroke. However, it is uncertain whether P‐wave parameters are associated with thrombus or spontaneous echo contrast in the left atrial appendage. Our study demonstrated a significant association of P‐wave duration, P‐wave dispersion, and advanced interatrial block with thrombus or spontaneous echo contrast in the left atrial appendage. IAB, interatrial block; PTFV1, P‐wave terminal force in V1.